Case Report: Primary cardiac synovial sarcoma invading the tricuspid valve in a pregnant woman - Li, Mixia; Huang, Maoxun; Piao, Hulin; Wang, Yong; Liu, Kexiang (Frontiers in Cardiovascular Medicine, 2024)
Primary cardiac synovial sarcoma (PCSS) is a rare and highly aggressive tumor with a significant mortality rate. Treatment guidelines has not been defined given the relative rarity of the condition, especially for pregnant women. Described herein is a 36-year-old pregnant woman at 29 weeks with gestation was as hospitalized due to chest tightness and nausea, and echocardiography found a mass involved the right heart and the tricuspid valve. She had to undergo cardiac surgery because the mass blocked almost the opening of the tricuspid valve.She underwent a radical resection of the masses and tricuspid valve, followed by replacement of the tricuspid valve with a mechanical valve. And she successfully delivered a healthy baby boy. The diagnosis of synovial sarcoma is confirmed by positive results indicating rearrangement of the SYT gene. The patient survived throughout the 30-month follow-up period. There are no reported cases of pregnant women diagnosed with cardiac synovial sarcoma and have undergone cardiac surgery and cesarean section. Our treatment plan not only maximizes patient survival but also ensures fetal survival. This situation is rare and needs documentation.